Corrosion Behavior of Copper Based Heat Exchanger Tube in Waters of Bangladesh Region at Varied Temperature and Flow Velocity - Rahman, M Muzibur; Ahmed, S Reaz (MIST International Journal of Science and Technology, 2020)
Heat exchangers used in the ships are mostly of water-cooled shell and tube type, whose tube stacks are made of copper-based materials due to the requirement of high corrosion resistance and high thermal conductivity. Even though, the copper made heat exchanger tubes do fail on board ships because of corrosion. More point of contention arises when it is manufactured by companies that have limited supporting data and documentations. In this context, the present paper investigates the corrosion behavior of copper tubes of heat exchanger to assess the life span of the tube stack for on-board applications. A series of experiments have been undertaken to investigate the corrosion rates of copper tubes in sea water and river water with flow velocity of 1.0 m/s, 1.5 m/s and 2.0 m/s for the tube side entry temperature of 20°C. The same experiments have been repeated for the shell side temperatures of 20°C, 40°C, 60°C and 80°C. The investigations have revealed that the corrosion in sea water is about three times higher than that of river water. The increases in temperature and flow velocity have increased the rate of corrosion to a significant level contributing to shorten the life span.